PENGHAMBAT KEMAMPUAN BERBAHASA INGGRIS DOSEN - Usada Usada (PAEDAGOGIA, 2008)
In order to develop their academic quality, it is very important for UNS'lecturers to improve English competency. It needs a conscientious management to reachthe goal of having English competency effectively. Based on the result of the interviewwith the lecturers who attend English course, it was found that there were some obstaclesin carrying out the English course. The data were collected by using questionnaire andinterview. The result of this research showed that there were some obstacles dealing withdeveloping lecturers’ English competency: (1) management factors, the time of Englishcourse activity often overlapped with lecturers' other activities, consequently it causedonly few participants attend the course; (2) the motivation of trainees factor, it showedthat they had low need of achievement. It can be seen fromsome indicators: a) they did notspend time to learn the material outside the classroom; b) they did not study English athome; c) they attended the course without preparation. Therefore the researcher proposedseveral suggestions: (1) it is crucial to improve coordination to hold the course atthe appropriate time; (2) it is necessary to motivate the trainees by giving rewards inconnection with improvement in career or promotion/rank.